The effect of mineral fertilization on heavy metals content in tomato fruit - Moigradean Diana; Poiana Mariana-Atena; Alda Liana Maria; Bordean Despina-Maria; Popa Viorica-Mirela; Alda Simion (2013)
The goal of our study was to investigate the effect of different mineral fertilization doses on the heavy metals content (Fe, Mn, Cu, Zn, Ni, Co, Cr, Pb and Cd) in tomato fruit grown in uncontaminated area. The heavy metals bioaccumulation rates have also been investigated. The experience was done in a cambric cernosium soil, with low acidity reaction, very good content in nitrogen, phosphorus and potassium and the high natural fertility potential favorable vegetables cultivation in Romanian Western Plain area. Also, this soil is very rich in iron, zinc, cooper and cobalt but fall below acceptable parameters under the laws of our country. The study was performed on control soil samples (without fertilizers) and soil samples after differentiated NPK fertilization in variable dozes: N30P30K30, N45P45K45 , N^P«,!^, and N12oP6oK6oAlthough the soil analyses showed the presence of cobalt, chromium and lead in certain concentrations, except for cadmium which is not detectable, in tomatoes grown in the investigated area these heavy metals not found. Other micronutrients were very low values, well below the legal maximum allowed in vegetables cultivated in Romania. These results suggest that this area is favorable to ecological vegetables crops.
Keywords: Természettudományok; Kémiai tudományok; Mezőgazdaság-tudományok; Mezőgazdaság, erdészet, halászat